Pengaruh Atribut Produk Terhadap Persepsi Konsumen: Studi Kasus Motor Merek Honda Jenis Vario pada PT. Kusumasejati Intiprima Cabang Bogor - Zuhdi, Saefudin; Supardi, Denny (Jurnal Ilmiah Ranggagading (JIR), 2009)
Marketing strategy conducted by the company in stimulating the companyâs good perception shaping is by developing product and its attributes comprising brand, package, phisical being et cetera which can be evaluated by consumers in harmony with value system, belief, and consumers experience as users. The goal of this research is to find out how are consumers perception toward the objects (company, product, or brand) and marketing strategy conducted by the company company, its product and its attributes. The result of the research shows that Honda brand motor product of dominant vario genre has influence (score on an average 4,16), its found that consumers perception to the attribute of Honda brand motor product of vario genre is âgoodâ (score on an average 4). Regression analysis result shows that function y = 46.694 + 0.326 (x), it can be used to predict if the grade of product attribute variable is 5, then it can be predicated that consumers perception is 48,324. Thereby it can be found out from correlation coefficient analysis result that motor product attribute has significant correlation to the perception of society with moderate and positive correlation (score 0,405) and the attribute product has contribution as high as 16,403 percent in influencing the perception of society. Keywords : Product attribute; Consumers Perception.